Evidence base multi-discipline critical strategies toward better tomorrow for very preterm infants - Hsiao-Yu Chiu; Shih-Ming Chu; Hsiang-Yu Lin; Ming-Luen Tsai; Yin-Ting Chen; Hung-Chih Lin (Elsevier, 2020)
Despite advances in neonatal intensive care in the recent decade, a large number of very preterm infants (VPIs) remain at risk for significant neurodevelopmental impairment (NDI). Given that there are many interventions need to be implemented during the critical perinatal period so that complications of these vulnerable VPIs could be minimized, it is urgent to develop multi-discipline strategies based on evidence to be carried out. The objective of this new term evidence-based perinatal critical strategies (EBPCS), is to provide beneficial intervention towards better neurodevelopmental outcomes, specifically for preterm infants below 28 weeks gestational age. EBPCS is defined as the management of the VPIs during the perinatal period which would include antenatal counseling with team briefing and share decision making, treat the chorioamnionitis, antenatal MgS04, antenatal steroid, delayed cord clamping/milking, neonatal resuscitation team preparation, prevention of hypothermia, immediate respiratory support with continuous positive airway pressure at delivery room, less invasive surfactant administration, early surfactant with budesonide therapy, support of cardiovascular system, early initiate of probiotics administration, early caffeine, early parenteral and enteral nutrition, promptly initiating antibiotics. These critical strategies will be discussed detail in the text; nonetheless, standardized protocols, technical skills and repeated training are the cornerstones of successful of EBPCS. Further experience from different NICU is needed to prove whether these very complicate and comprehensive perinatal critical strategies could translate into daily practice to mitigate the incidence of NDI in high-risk VPIs.